FEMINISME SASTRA: MENGUNGKAP CITRA PEREMPUAN DAN KETIDAKADILAN GENDER DALAM PROSA - Yunarti, Yuni; Amalia, Nafisa; Elvina, Nara Prisya; Puspaningrum, Syafira; Masrukah, Siti; Julianto, Indra Rasyid (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2025)
Women are often used as symbols of life, but often experience violence and injustice, and are considered second-class creatures after men. The problems inherent in women actually make them a source of inspiration in literary works, because women have two contrasting sides. Literary works become a medium that can describe various aspects of women's lives. This research was conducted with a literature study method using a qualitative descriptive approach. Literature study is a research method that aims to obtain data and information through literature review, recording, and reviewing various reference books and other written sources. The purpose of this study is to identify the image of women and forms of gender injustice in the novel. The results show that the image of women can be described as meek, caring, tough, brave, easy to worry, responsible, and independent. Meanwhile, the forms of gender injustice found include marginalisation, subordination, stereotyping, and violence. In literary works, women are often used as main characters with various images reflected through their daily lives. The image of women is an interesting study because it reflects a diverse personality and is a source of inspiration. Gender injustice itself is a form of discrimination against men and women, but in reality, women are more often the victims, because there is still an assumption that women are weak creatures.